The art of union and disunion in the Houses of Parliament, 1834-1928 - Ford, James (2016)
This thesis explores the importance of the United Kingdom’s composition as a multinational state to the decoration of the new Houses of Parliament, constructed by Sir Charles Barry following the destruction of most of the old Palace of Westminster by fire in 1834. Over seven chapters, it examines the decorative schemes undertaken between the 1840s and 1860s by Barry and the Fine Arts Commission, followed by later, individual programmes, the last of which was completed in 1928.